IN-VITRO ANTIOXIDANT ACTIVITY OF CANNA INDICA EXTRACTS USING DIFFERENT SOLVENT SYSTEM - Singh, Rajat; Singh, Utkarsh; Bachheti, Rakesh Kumar; Saini, Chandra Kiran (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: To investigate the antimicrobial and antidiabetic potential of canna indica plant extracts. Methods: In the present research work the selected plant i.e. Canna indica L. Cannaceae was collected, dried and extracted with different solvents. Different test were performed for the presence of different phytochemicals. The antimicrobial activity was determined by agar well-diffusion method. The extracts were evaluated for antidiabetic activity by using alpha-amylase and alpha-glucosidase enzyme inhibition method. Results and conclusion: The findings of the present study indicate that C. indica extracts contain secondary metabolites which have potent antimicrobial and antidiabetic activities comparable to standard drugs. This information may help to develop potent bioactive compound(s) in the pharmaceutical industry for the development of drugs.